The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1109/lra.2023.3240362
|View full text |Cite
|
Sign up to set email alerts
|

i2c-net: Using Instance-Level Neural Networks for Monocular Category-Level 6D Pose Estimation

Abstract: Object detection and pose estimation are strict requirements for many robotic grasping and manipulation applications to endow robots with the ability to grasp objects with different properties in cluttered scenes and with various lighting conditions. This work proposes the framework i2c-net to extract the 6D pose of multiple objects belonging to different categories, starting from an instance-level pose estimation network and relying only on RGB images. The network is trained on a custom-made synthetic photo-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Indeed, the statistics shown by the BOP benchmark reported that the scores suffered from a huge drop even at low levels of occlusion, as demonstrated by the 30% gap of difference in performance obtained in LINEMODE and Occluded-LINEMODE that provides the same objects but partially occluded. Estimating the 6D pose of objects is an active field with important practical implications, and after 2018, other works [18], [19] have been published, showing a margin of improvement for several aspects. Therefore, the authors believe that in the near future, such methods can be employed for the proposed benchmark to automatically detect the occlusion percentage of cluttered scenes in the evaluation metric, but in the meanwhile, manual segmentation guarantees more accurate measurements.…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…Indeed, the statistics shown by the BOP benchmark reported that the scores suffered from a huge drop even at low levels of occlusion, as demonstrated by the 30% gap of difference in performance obtained in LINEMODE and Occluded-LINEMODE that provides the same objects but partially occluded. Estimating the 6D pose of objects is an active field with important practical implications, and after 2018, other works [18], [19] have been published, showing a margin of improvement for several aspects. Therefore, the authors believe that in the near future, such methods can be employed for the proposed benchmark to automatically detect the occlusion percentage of cluttered scenes in the evaluation metric, but in the meanwhile, manual segmentation guarantees more accurate measurements.…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…The boom of deep learning has significantly improved object pose estimation. A series of methods have been proposed to holistically estimate object poses from monocular color images [1], [26], [27], [28] or with the aid from depth sensors [29], [30], [31], [32], [33], [34]. These methods took advantage of the CNNs' regression ability to learn mapping functions from the observed images to object poses.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, an important goal in this ongoing industrial revolution is to make such algorithms robust to clutter to increase the flexibility of the next-generation of robots. Estimating the pose of objects is an active field with important practical implications, and in the last years, some works ( Song et al, 2020 ; Remus et al, 2023 ) have been published showing a margin of improvement for several aspects.…”
Section: Introductionmentioning
confidence: 99%